2020
DOI: 10.1101/2020.03.03.975037
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hsp27 reduces glycation-induced toxicity and aggregation of α-synuclein

Abstract: α-synuclein (aSyn) is a major player in Parkinson's disease (PD) and a group of other disorders collectively known as synucleinopathies, but the precise molecular mechanisms involved are still unclear. aSyn, as virtually all proteins, undergoes a series of posttranslational modifications (PTMs) during its lifetime which can affect its biology and pathobiology. We recently showed that glycation of aSyn by methylglyoxal (MGO) potentiates its oligomerization and toxicity, induces dopaminergic neuronal cell loss i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Studies have demonstrated the colocalization of HSP27 with αsynuclein in amyloid fibrils, implicating its involvement in PD pathology. The levels of HSP27 are vital for modulating glycation-associated cellular pathologies in synucleinopathies via its binding and inhibition of amyloid nucleation, fibril binding, and fibril disaggregation [272,273]. As an important regulator of cell survival and its role in different cellular functions in normal and stressful conditions, HSP27 is now considered as an important therapeutic target and biomarker in various human diseases.…”
Section: Small Heat Shock Proteins (Hspb)mentioning
confidence: 99%
“…Studies have demonstrated the colocalization of HSP27 with αsynuclein in amyloid fibrils, implicating its involvement in PD pathology. The levels of HSP27 are vital for modulating glycation-associated cellular pathologies in synucleinopathies via its binding and inhibition of amyloid nucleation, fibril binding, and fibril disaggregation [272,273]. As an important regulator of cell survival and its role in different cellular functions in normal and stressful conditions, HSP27 is now considered as an important therapeutic target and biomarker in various human diseases.…”
Section: Small Heat Shock Proteins (Hspb)mentioning
confidence: 99%